The Effect Of Therapeutic Communication On The Anxiety Level Of The Elderly - Deviantony, Fitrio; Kurniyawan, Enggal Hadi; Alifia Marcheilla Yulfansha; Aura Najwa Salasabila; Adhelia Reisa Zalsabilla; Dewi, Erti Ikhtiarini; Fitria, Yeni (Rajaki of Tulip Medika Publisher, 2024)
Introduction: Anxiety disorders have a high incidence rate in the elderly, with the most significant factor being thinking about the disease they are suffering from. This requires therapeutic communication to build a nurse-patient relationship with the elderly to adapt to psychological disorders, including anxiety, to relieve and make elderly patients feel comfortable, ultimately speeding up their recovery. Goals: Aimed at evaluating the effectiveness of therapeutic communication in reducing anxiety levels in the elderly. Method: A review article was conducted based on research issues and methodology, with article searches using the PICO framework strategy using the Google Scholar, Springer, ResearchGate, and Semantic Scholar databases. Results: The results of the study show that anxiety is a common problem often experienced by the elderly during the aging process. Some factors that trigger anxiety in the elderly include health issues and a lack of social interaction due to death or relocation. The research indicates that therapeutic communication can help reduce anxiety levels in the elderly. Good therapeutic communication by healthcare professionals has a positive impact on reducing patient anxiety. Discussion: In this regard, the researcher highlights the importance of therapeutic communication in reducing anxiety in the elderly. Both verbal and nonverbal therapeutic communication is considered a key element in nursing care. Additionally, the researcher emphasizes the importance of adopting different approaches when applying therapeutic communication techniques to the elderly. Unstable emotional reactions and communication barriers pose specific challenges in interacting with the elderly.